2022
DOI: 10.3390/ijms231911528
|View full text |Cite
|
Sign up to set email alerts
|

Improved Trimethylangelicin Analogs for Cystic Fibrosis: Design, Synthesis and Preliminary Screening

Abstract: A small library of new angelicin derivatives was designed and synthesized with the aim of bypassing the side effects of trimethylangelicin (TMA), a promising agent for the treatment of cystic fibrosis. To prevent photoreactions with DNA, hindered substituents were inserted at the 4 and/or 6 positions. Unlike the parent TMA, none of the new derivatives exhibited significant cytotoxicity or mutagenic effects. Among the synthesized compounds, the 4-phenylderivative 12 and the 6-phenylderivative 25 exerted a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The TMA analogues were synthesized as previously reported [18,19]. The GY971 derivative (6-p-aminophenyl-4,4 -dimethyl-angelicin, also called pANDMA), is characterized by an aniline moiety at position 6 of the furocoumarin structure (Figure 2).…”
Section: Synthesis Of Tma Analoguesmentioning
confidence: 99%
See 3 more Smart Citations
“…The TMA analogues were synthesized as previously reported [18,19]. The GY971 derivative (6-p-aminophenyl-4,4 -dimethyl-angelicin, also called pANDMA), is characterized by an aniline moiety at position 6 of the furocoumarin structure (Figure 2).…”
Section: Synthesis Of Tma Analoguesmentioning
confidence: 99%
“…The GY971 derivative (6-p-aminophenyl-4,4 -dimethyl-angelicin, also called pANDMA), is characterized by an aniline moiety at position 6 of the furocoumarin structure (Figure 2). The amino group, salified as mesylate salt, allowed the formation of a water-soluble derivative: the hydrophilic mesylate, named GY971a, demonstrated to be four-times more bioavailable than the parent GY971 [19]. Instead, typically all the TMA analogues were lipophilic and solubilize only in DMSO.…”
Section: Synthesis Of Tma Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, TMA shows serious disadvantages, such as poor solubility, phototoxicity, and mutagenicity. To overcome these side effects, Vaccarin et al [ 17 ] designed and synthesized a library of TMA analogs. The authors showed that bulky aromatic substituents at C-4 of TMA impaired DNA intercalation and prevented the photoreaction of the lactone or furan double bond of the furocoumarin scaffold with the nucleic acid.…”
mentioning
confidence: 99%